2016
DOI: 10.1094/pdis-11-15-1332-re
|View full text |Cite
|
Sign up to set email alerts
|

Angular Leaf Spot of Cucurbits is Associated With Genetically DiversePseudomonas syringaeStrains

Abstract: Angular leaf spot of cucurbits is generally considered to be caused by Pseudomonas syringae pv. lachrymans. It has a worldwide distribution and has been observed to emerge sporadically under humid and wet conditions. Reports of multiple P. syringae pathovars associated with the disease and lack of molecular analysis has left the true diversity of populations in the United States unclear. In this study, we collected 27 P. syringae strains causing foliar lesions and blighting on watermelon, cantaloupe, and squas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Furthermore, in these tests some of the most aggressive strains on pea were those closely related to strains from pea but that had been isolated from other diseased plants including lilac, common bean, hairy vetch and cantaloupe (Martin-Sanz et al 2013). Several independent studies on P. syringae causing blights to cucurbits have revealed that there is a wide genetic diversity of strains from epidemics to cantaloupe, squash and watermelon and that the strains are virulent to numerous cucurbit species as well as to other herbaceous plants (Morris et al 2000;Sedighian et al 2014;Newberry et al 2016). These examples raise questions about the extent of cross contaminations and spill over.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in these tests some of the most aggressive strains on pea were those closely related to strains from pea but that had been isolated from other diseased plants including lilac, common bean, hairy vetch and cantaloupe (Martin-Sanz et al 2013). Several independent studies on P. syringae causing blights to cucurbits have revealed that there is a wide genetic diversity of strains from epidemics to cantaloupe, squash and watermelon and that the strains are virulent to numerous cucurbit species as well as to other herbaceous plants (Morris et al 2000;Sedighian et al 2014;Newberry et al 2016). These examples raise questions about the extent of cross contaminations and spill over.…”
Section: Introductionmentioning
confidence: 99%
“…These strains were isolated from watermelon and squash grown in six different Florida counties during these epidemics and comprised haplotypes one and two (Newberry et al, 2018). Three strains included for sequencing comprised haplotype three and were isolated from cantaloupe and squash grown in Florida, Georgia, and California between 2000 and 2006 (Newberry et al, 2016). Finally, three additional strains that were isolated from symptomatic squash grown in Italy, Serbia, and China between 2005 and 2013 were also sequenced because they were found to be identical at four partial housekeeping gene sequences to one of the previously mentioned haplotypes (Hwang et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…syringae type/pathotype strain, LMG 1247 PT (=ICMP 3023 T ), within phylogroup 2b. Additionally, we identified two other clonal lineages collected from either the same, or previous bacterial leaf spot epidemics in the United States that shared a recent a common ancestor with the aforementioned epidemic clone; however, were located in a separate phylogroup within the same species, namely phylogroup 2a (Newberry et al, 2016, 2018). Although, we were able to precisely classify these pathogens within the phylogenetic structure of P. syringae sensu lato using MLSA, we were unable to delineate them from other strains collected from a diverse group of plant species or attribute them to any pathovar previously associated with cucurbit hosts, other than P. syringae pv.…”
Section: Introductionmentioning
confidence: 99%
“…2b). It is interesting to note that Newberry et al (2016) demonstrated that some strains associated with angular leaf spot in cucurbits are phylogenetically distinct from pathovar lachrymans. Strain classification is also an issue in other pathovars.…”
Section: Discussionmentioning
confidence: 99%
“…bacterial angular leaf spot, is distributed worldwide and appears on other cucurbit species as well. Novel haplotypes of P. syringae were observed to be common on multiple cucurbit hosts, thus illustrating this species' large ecological diversity (Newberry et al 2016). Moreover, pathovar lachrymans is particularly detrimental because it can facilitate infection by Pseudoperonospora cubensis, which is the most destructive cucumber pathogen that causes downy mildew (Olczak-Woltman et al 2008).…”
Section: Introductionmentioning
confidence: 96%